Adaptive coordinated tracking control for multi-robot system with directed communication topology. (28th November 2017) - Wang, Qin; Chen, Zuwen; Yi, Yang
In this article, an adaptive coordinated tracking control problem for a group of nonholonomic chained systems has been discussed under the assumption that the desired trajectory is available only to a part of neighboring agents. Firstly, coordinated tracking controllers under the directed communication topology graph containing a spanning tree are designed for two subsystems, adaptive control gains are employed in the linear subsystem based on the state information of neighboring agents, then the global information of the topology graph is not required to be known in the control laws. Furthermore, the backstepping strategy is applied in the rest of chained-form subsystem such that the state of all robots converge to the desired reference trajectory. And then, the results are further evolved with the case of switching topology. Finally, an application is introduced and the simulation results are given to show the validity of the proposed theoretical results.